Pengaruh Konten Instagram @visit.tangsel Terhadap Promosi Pariwisata Kota Tangerang Selatan - Saputra, Muhammad Febrian; Raymond, Andree (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Tourism is an important sector for Indonesia, tourism has an important role for the country as a fairly large foreign exchange income. Urban areas such as Jabodetabek not only have multi-storey buildings, but also have attractive tourism destinations. Not only Jabodetabek, the city of South Tangerang also has a lot of natural beauty that is no less interesting. Instagram is used as a very appropriate media to promote interesting places that many people don't know about with a very wide reach, one of which is visit.tangsel which is an Instagram account that promotes destinations, culinary delights, accommodation, culture and interesting places around the city South Tangerang. The purpose of this research is to see whether there is an influence and how significant the influence is given by the Instagram account @visit.tangsel in promoting tourism in the city of South Tangerang. Based on this, researchers are interested in conducting research. This research uses quantitative research methods and uses a method of distributing questionnaires to followers of the Instagram account @visit.tangsel as many as 100 respondents, 90 respondents were obtained using probability sampling techniques, namely simple random sampling and 10 respondents were obtained from convenience sampling, data analysis methods, validity tests, reliability tests and simple linear regression test, the data that has been collected is obtained using the SPSS 25 application. With the results of simple linear regression Y= 15.880 + 0.439X with a significance value of 0.000 based on the results of the research that has been carried out. This research shows that the Instagram account @visit.tangsel has a positive influence on tourism promotion in the city of South Tangerang.